Advanced medical life support : an assessment-based approach - course manual - National Association of Emergency Medical Technicians (U.S.) (Burlington, MA : Jones & Bartlett Learning, 2021)
"NAEMT's Advanced Medical Life Support (AMLS) course is the first EMS education program that fully addresses how to best assess and manage the most common medical crises in patients, offering a "think outside the box" methodology. It is for all levels of practitioners with a strong commitment to patient care, including emergency medical technicians, paramedics, nurses, nurse practitioners, physician assistants, nurse anesthetists and physicians"--
Advanced medical life support assessment for the medical patient -- Respiratory disorders -- Cardiovascular disorders -- Shock -- Neurological disorders -- Abdominal disorders -- Endocrine and metabolic disorders -- Infectious diseases -- Environmental disorders -- Toxicology, hazardous materials, and weapons of mass destruction -- Sepsis -- Medication/pharmacology.
Includes bibliographical references and index.
Keywords: Emergency Medical Services; Emergencies; Needs Assessment; Emergency Medical Technicians; Advanced Trauma Life Support Care -- methods